Core approach into the development of interactive multimedia learning environment learning of Al-Quran / Nor Faeza Sharudin - Sharudin, Nor Faeza (2006)
As time goes by, the technology also raise rapidly. Therefore, there are many new applications and technology exist especially things that relate to education. Unfortunately, schools are lag behind as there are stilt implementing the use of textbooks and blackt>oards on a daily basis. Computer, for example is being used widely as integrated teaming technologies because it is believed can open up vast amounts of resources for student. (Duffin and Mac Rorie, 1998) Meanwhile the implementation of interactive multimedia allows the contents to be presented in a nonlinear way in which user involve actively in each leaming session. This project is focusing on leaming al-Quran through iqra' method. For simple explanation, it is about to implement iqra' method with constructivism through CORE approach. It is to create a leamer centered environment among students. However, after research has been done, the researcher found that iqra' can be implemented using CORE approach. It is because, with all the element in leaming iqra' using iqra' can be delivered successfully